Pengaruh Religiusitas, Agreeableness, dan Usia Terhadap Perilaku Prososial Remaja - Ika Maya Widiastuti (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2021)
This study aims to examine the effect of religiosity, agreeableness, and age on adolescence’s prosocial behavior. This study selected the sample of 296 student, using a purposive sampling technique. The data collection used modification scale of Prosocialness Scale, Muslim Daily Religiosity Assessment Scale (MUDRAS), and International Personality Item Pool-Big Five Factors Model-50 (IPIP-BFM-50). Multiple regression and Confirmatory Factor Analysis (CFA) were performed to analyze the data. The finding showed there is a significant influence of religiosity, agreeableness, and age on prosocial behavior.